Frequency-Dependent Dielectric Polarizability of Flexible Polyelectrolytes in Electrolyte Solution: A Dissipative Particle Dynamics Simulation. Issue 9 (2nd May 2019) - Jung, Gerhard; Kasper, Sebastian; Schmid, Friederike
Abstract : We study the frequency-dependent dielectric polarizability of flexible polyelectrolytes in electrolyte solution by Dissipative Particle Dynamics (DPD) simulations, focusing on the contribution of the electric double layer (EDL) that surrounds the polyelectrolyte. The simulations are based on a recently proposed mesoscopic model that treats the microions in solution at the level of density clouds and solves the corresponding electrokinetic equations using pseudo-particles. The ion diffusivity and the solvent quality are varied systematically. Both factors are found to significantly influence the dielectric properties of the polyelectrolyte: The diffusion of co- and counterions reduces concentration gradients associated with the polarization of the EDL. As a result, the polarizability is a non-monotonic function of the frequency, and in the low-frequency limit, it decreases with increasing ion diffusivity. The solvent quality influences the degree of chain swelling and thus the shape of the EDL. This affects the polarization of the loosely bound co- and counterions in the outer layers of the EDL and leads to a sub-linear scaling of the polarizability with the polyelectrolyte chain length in bad solvent.